The institutional educational project and educational management in the I.E. Our Lady of Carmen of the Imperial district, 2023 - Audante Vicente , Pedro Pablo (2024)
The present research raises a problem that, although it has deserved the attention of other researchers, maintains its validity due to the particularities that characterize the different educational institutions and the responsibility that they have towards their respective communities and their role in the National educative system. The various investigations on the subject report, according to their own results, the degree of link between PEI and school management, but, considering that each Educational Institution has its own reality, the study in question always sheds new light. Thus, in this study, results have been found that show contradictions in the conception of the PEI and whose impact on educational management leads to deficits in the quality of the educational service.